Identifying Opportunities for Swedish Component and Service Suppliers within the US Wind Energy Industry - Nachemson, Louise; Sundqvist, Linda (My University, 2010)
This master thesis provides an overview of the US wind energy industry through an innovation system analysis thus covering both policy development as well as industry development. It focuses on the recent years of extraordinary growth of installed wind capacity that the US has experienced and the bulk of the empiric data focuses on four broader context issues; policy issues, electrical infrastructure, technology development and the industry supply chain development. The outcome of the Innovation Systems analysis is interpreted as potential business opportunities for Swedish component and service suppliers and the analysis also elaborates on some potential entry strategies as well as barriers.
Keywords: Miljöteknik; Environmental engineering